Genotoxic endpoints in the earthworms sub-lethal assay to evaluate natural soils contaminated by metals and radionuclides - Lourenço, Joana I. (2019)
Eisenia andrei was exposed, for 56 days, to a contaminated soil from an abandoned uranium mine and to the natural reference soil LUFA 2.2. The organisms were sampled after 0, 1, 2, 7, 14 and 56 days of exposure, to assess metals bioaccumulation, coelomocytes DNA integrity and cytotoxicity. Radionuclides bioaccumulation and growth were also determined at 0 h, 14 and 56 days of exposure. Results have shown the bioaccumulation of metals and radionuclides, as well as, growth reduction, DNA damages and cytotoxicity in earthworms exposed to contaminated soil. The usefulness of the comet assay and flow cytometry, to evaluate the toxicity of contaminants such as metals and radionuclides in earthworms are herein reported. We also demonstrated that DNA strand breakage and immune cells frequency are important endpoints to be employed in the earthworm reproduction assay, for the evaluation of soil geno and cytotoxicity, as part of the risk assessment of contaminated areas. This is the first study that integrates DNA damage and cytotoxicity evaluation, growth and bioaccumulation of metals and radionuclides in a sub lethal assay, for earthworms exposed to soil contaminated with metals and radionuclides.